Interleukin‐10 gene –627 allele variants, not interleukin‐I beta gene and receptor antagonist gene polymorphisms, are associated with atopic bronchial asthma - Hang, Liang‐Wen (J Clin Lab Anal, 2003)
Asthma is an airway hyperresponsive disease characterized by the expression of multiple inflammatory genes, including cytokines. Interleukin‐I and interleukin‐10 (IL‐1 and IL‐10) are cytokines that might play a role in the process of inflammation and are therefore considered to be involved in the pathogenesis of bronchial asthma. The aim of this study was to test whether the polymorphisms of the promoter region and exon 5 of the IL‐1 gene, intron 2 of the IL‐1Ra gene, and –627 nucleotide (C/A) of the IL‐10 gene could be genetic markers for the susceptibility of bronchial asthma. A normal control group made up of 47 healthy volunteers and 117 patients with bronchial asthma were examined in this study. We analyzed the variable number of tandem repeats at intron 2 of the IL‐1Ra gene for the polymorphisms by polymerase chain reaction (PCR). PCR‐based restriction analysis of the IL‐1 gene polymorphisms of the promoter region and exon 5 was carried out by the endonucleases Ava I and Taq I, respectively. The IL‐10 gene –627 C/A polymorphisms were investigated by PCR‐based restriction analysis. The distribution of CC homozygotes in the IL‐10 gene was significantly lower in asthma patients than in controls (P=0.013, OR=3.599, 95% CI=1.240∼10.441). The polymorphisms studied in the IL‐1 genes did not reveal any significant association with bronchial asthma when compared with the control group (promoter region by chi‐square test, P=0.627; exon 5 region by Fisher's exact test, P=0.403). Only two alleles of the IL‐1Ra gene corresponding to one and two copies of an 86‐base pair sequence repeat were identified by PCR in the control group. There were three alleles found in the asthmatic patient group. The results revealed no significant differences between normal individuals and asthma patients (P=0.454, Fisher's exact test). The IL‐10 gene –627 “A” allele is an associated risk factor of developing atopic asthma. J. Clin. Lab. Anal. 17:168–173, 2003. © 2003 Wiley‐Liss, Inc.